2018
DOI: 10.1021/acssuschemeng.8b02841
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Stability of Engineered Biochar-Based Phosphate Fertilizers

Abstract: Converting abundant agricultural residues to valuable products, such as biochar, is a pressing challenge for society. Here, our objective has been to produce biochar-based fertilizers (BBFs) with high carbon stability, high yield, and characteristics favorable for their use in soils. Thus, H 3 PO 4 with and without MgO was co-pyrolyzed with coffee husk and poultry litter. Proximate analysis, total phosphorus and magnesium, biochar yield, carbon retention, and thermal and chemical carbon stability were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…These authors showed a much slower P release rate as compared to TSP and also a similar maize yield in a pot experiment. Additionally, Carneiro et al (2018) observed that co-pyrolysis of biomass with phosphate sources increased the yield of biochar and also increased the carbon retention during pyrolysis and carbon chemical and thermal stability. Future studies should be focused on testing novel binding agents during the granulation process, which can control the release behavior of P over time favoring the P uptake by the plant throughout the cultivation, thus improving the efficiency of use of soluble-P fertilizers.…”
Section: Greenhouse Pot Experimentsmentioning
confidence: 99%
“…These authors showed a much slower P release rate as compared to TSP and also a similar maize yield in a pot experiment. Additionally, Carneiro et al (2018) observed that co-pyrolysis of biomass with phosphate sources increased the yield of biochar and also increased the carbon retention during pyrolysis and carbon chemical and thermal stability. Future studies should be focused on testing novel binding agents during the granulation process, which can control the release behavior of P over time favoring the P uptake by the plant throughout the cultivation, thus improving the efficiency of use of soluble-P fertilizers.…”
Section: Greenhouse Pot Experimentsmentioning
confidence: 99%
“…The pyrolysis of PL enriched with H 3 PO 4 + MgO caused a decrease in the pH of the PLB (from 8.3 in PL to 6.1 in PLB). Normally, pristine pure PL biochar tends to be highly alkaline (pH~11), and when it was impregnated with H 3 PO 4 in combination with MgO, the acidity of the P source was neutralized [17,21]. The total P content increased considerably with the impregnation of H 3 PO 4 and MgO (Table 2), reaching values as high as those in conventional P fertilizers.…”
Section: Properties Of the Biochar-based Fertilizersmentioning
confidence: 99%
“…The physical characteristics of biochar such as the number of pores, pore layout, and specific surface area are influenced by the raw material and affect the availability of nutrients in soil [38]. Furthermore, the co-pyrolysis of PL with H 3 PO 4 + MgO increases the surface area and small pores [17] that can potentially promote the link between urea and surface functional groups through chemical reactions. Pores are formed by the decomposition of organic macromolecules and give PLB the ability to accommodate urea molecules [37].…”
Section: Scanning Electron Microscopy (Sem) and Energy-dispersive X-ray Spectroscopy (Edx) Analysismentioning
confidence: 99%
See 2 more Smart Citations